Comparison of exposure estimates in the Finnish job-exposure matrix FINJEM with a JEM derived from expert assessments performed in Montreal. Issue 7 (1st April 2012) - Lavoué, Jérôme; Pintos, Javier; Van Tongeren, Martie; Kincl, Laurel; Richardson, Lesley; Kauppinen, T; Cardis, Elisabeth; Siemiatycki, Jack
Abstract : Context: Retrospective exposure assessment in population-based case–control studies poses a major challenge due to the wide range of occupations and industries involved. The FINJEM is a generic job-exposure matrix (JEM) developed in Finland, which represents a potentially cost-effective exposure assessment tool. While FINJEM has been used in several studies outside Finland, little is known of its applicability in other countries. Methods: We compared prevalence and intensity of exposure in FINJEM with a JEM developed from expert assessments of occupational histories obtained in a population-based case–control study in Montreal. Agreement for prevalence of exposure was measured by weighted κ coefficients between prevalence categories. Agreement for exposure intensity was measured by Spearman correlation coefficients between cells with non-null exposure. Results: The comparison involved 27 chemicals, the time period 1945–1995 and included 4743 jobs initially assessed by the Montreal experts. 4293 combinations of agent, occupational title and period were available for comparison of prevalence. Agent-specific prevalence was consistently higher in the Montreal JEM (median difference 1.7%). Agent-specific κ values between prevalence categories varied from 0.89 (welding fumes) to 0.07 (flour dust). The comparison of exposure levels involved 14 agents and 198 cells with non-null exposure in both sources. Agent-specific Spearman correlation varied from 0.89 (flour dust) to −0.35 (benzo(a)pyrene). Conclusion: Our observations suggest that information concerning several agents (eg, metals, welding fumes) can be successfully transported from Finland to Canada and probably other countries. However, for other agents, there was considerable disagreement, and hence, transportability of FINJEM cannot be assumed by default.